Explaining the relations between culture, structure and agency in lecturers' contribution and non-contribution to Open Educational Resources in a higher education institution - Cox, Glenda (School of Education, 2016)
Despite the existence of many successful initiatives to promote the sharing and use of Open Educational Resources (OER), sharing and use of OER is not a widely accepted practice in higher education. The reasons for lecturers' choices on whether or not to contribute OER are poorly understood. This thesis develops a theoretically-based explanation of both why lecturers contribute and why they do not. The thesis addresses the question: How do the relations between culture, structure and agency influence lecturers' contribution and non-contribution of OER in a higher education institution? A mixed methods approach was used to gather quantitative (questionnaires) and qualitative (interviews) data. Fourteen lecturers from the University of Cape Town (UCT) were interviewed (two from each of its seven faculties), seven who had contributed OER and seven who had not. The analysis adopted an Activity Theory framework to highlight the enablers and barriers to contribution present in the institutional system. The Social Realism of Margaret Archer (1995, 2003, 2007a, 2012) was used to explore the power of academics' agency and their internal conversations arising from their personal concerns in deciding on their courses of action. This study illustrates how capturing lecturers' internal conversations and analysing how they think about their social contexts is valuable not only in the context of OER but also as a way of understanding their role as social actors more generally. Analysing the relations between culture, structure and agency in institutions explains why some institutions are slow to change and/or prefer to maintain current practices. At UCT, where institutional culture allows academic freedom of choice and structure supports that choice, it is the academic agents themselves who hold the power of action to contribute or not to contribute OER. Academics have the power to change their practice if it makes sense in terms of their projects, the activities that they are involved in and their concerns. Thus in this context, the long term sustainability of the OER movement rests firmly on the willingness of individual lecturers to share and use OER. By understanding the institutional context in which the individual is placed, OER can be encouraged appropriately